Quality is still free making quality certain in uncertain times - Crosby, Philip B. (McGraw-Hill, 1996)
This work provides an analysis of the author's entrepreneurial experiment in which he took quality ideas learned in corporate settings and adapted them to the business world at large. It re-examines concepts such as The 5 Erroneous Assumptions about Quality and Zero-Defects Mantra.